2020
DOI: 10.1016/j.respol.2019.103914
|View full text |Cite
|
Sign up to set email alerts
|

Inventor migration and knowledge flows: A two-way communication channel?

Abstract: This paper documents the influence of networks of highly skilled migrants on the international diffusion of knowledge-particularly those with degrees and occupations in science, technology, engineering and mathematics. It investigates knowledge inflows to host countries brought in by skilled immigrants. It then explores knowledge feedback to home countries generated by these migrants. We test our hypotheses in a country-pair gravity model setting, for the period 1990-2010, using patent citations across countri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(15 citation statements)
references
References 87 publications
1
12
0
Order By: Relevance
“…Importantly, these migrant networks work as a "knowledge bridge" between the home and host countries. Similar results are found in Marino et al (2020) and Miguelez and Noumedem Temgoua (2020) and can be observed in internal migration within a country. Kim and Lee (2019) have similar findings in analyzing a large panel of 154 countries from 1990 to 2011 that focuses on the networks that skilled immigrants from both in their home country as well as the country they emigrate to.…”
Section: Do More Highly Skilled Workers Cause Innovation?supporting
confidence: 88%
“…Importantly, these migrant networks work as a "knowledge bridge" between the home and host countries. Similar results are found in Marino et al (2020) and Miguelez and Noumedem Temgoua (2020) and can be observed in internal migration within a country. Kim and Lee (2019) have similar findings in analyzing a large panel of 154 countries from 1990 to 2011 that focuses on the networks that skilled immigrants from both in their home country as well as the country they emigrate to.…”
Section: Do More Highly Skilled Workers Cause Innovation?supporting
confidence: 88%
“…In a recent study, Miguelez and Noumedem Temgoua (2019) argue that migrant inventors, especially those employed in science, technology, engineering and mathematics fields (STEM migration) represent important channels of knowledge production and diffusion. Therefore, policymakers should focus more on finding strategies which support and consolidate relations between STEM migrants and non-migrant fellows, through suitable knowledge networks, in both sending and receiving country.…”
Section: 1 Positive Effects (Optimal/ Beneficial Brain Drain )mentioning
confidence: 99%
“…In addition, this study, in contrast to those listed below, focuses on the individual experience of academics, as the central agents of both intellectual capital management processes and academic migration. It is the factors of personal motivation and intentions, according to researchers, that reflect the trends of academic migration most fully and can be used for predicting and further factor analysis of this process in quantitative research (Vangen, C., 2016;Van Holm, Wu and Welch, 2019;Tarasyev and Agarkov, 2019;Miguelez and Temgoua, 2020).…”
Section: Introductionmentioning
confidence: 99%